COMPLICATIONS LIEES AU DYSFONCTIONNEMENT RENAL CHEZ LES PATIENTS HYPERTENDUS - GOUAICH, Hadja; M’BAREK, Khewla (My University, 2024)
The present research focused on the prevalence of chronic renal failure in a cohort of 30 dialysis patients with hypertension. The aim was to identify the main risk factors associated with impaired renal function in this small group. Analysis revealed that a significant number of these 30 patients showed signs of moderate to severe renal impairment. The results revealed that advanced age, concomitant diabetes or obesity, proteinuria and poor blood pressure control were major determinants of impaired renal function in this small cohort. Although based on a limited sample, this preliminary study highlights the need for early, comprehensive management of cardiovascular and renal risk factors to prevent the onset and progression of chronic renal failure in hypertensive patients.
Keywords: Chronic renal failure; Hypertension; Diabetes; Dialysis